Capacity development in practice - Ubels, Jan, 1956-; Acquaye-Baddoo, Naa-Aku; Fowler, Alan, 1947- (Earthscan, 2010)
The international development community invests billions of dollars to improve organisational capacity. But real-life practice is poorly understood and undervalued as a distinct professional domain. Written by practitioners, this innovative publication is designed to make capacity development more professional and increasingly effective in achieving development goals. Practical illustrations draw on experiences from the civic, government and private sectors. A central theme is to understand capacity as more than something internal to organisations. This book shows how capacity also stems from ...